Rahasia Wanita: Sebuah Konsep Menuju Keutamaan dalam Serat Wara Ratna - Izza, Maulana Nurul; Nugroho, Yusro Edy (Jurnal Bahasa dan Sastra, 2024)
Women have a noble position In Javanese view. Therefore, it is important for women to understand their position so that conflict does not occur in the household. This study aims to analyze the conceptual foundations of the position of Javanese women in the text serat Wara Ratna by Pakubuwana IX. This study is qualitative study with genetic structuralism. The data source for this study is the Wara Ratna serat text with catalog number code RP 108.0 306 which is stored at the Radya Pustaka Museum, Surakarta. The data collection technique was carried out using literature study in the form of heuristic reading of Javanese text. The data analysis technique was carried out using content analysis. The study results show that the position of women in the Wara Ratna serat is as secret keepers. Women are seen as figures that are full of secrets. These secret is between a woman and herself, her husband, family and other people. The results of this study can be used as a reference for forming teaching values regarding the position of women in the Javanese view.